PENINGKATAN PEMAHAMAN KONSEP MELALUI PENDEKATAN REALISTIC MATHEMATICS EDUCATION BERBANTUAN GEOGEBRA MATERI BANGUN RUANG - Sigit Wibowo; Bagus Adi Saputro; Achmad Buchori (Jurnal Lingkar Mutu Pendidikan, 2025)
The study aims to describe the effectiveness of the Realistic Mathematics Education approach assisted by GeoGebra based on the difference, classical completeness, and student’s concept comprehension gain in solid geometry lesson. This research is a quasi-experimental research with a Nonequivalent Control Group Design. The population in this study consists of fourth-grade Elementary Schools students in Gugus Pangeran Diponegoro, Warungasem District. The samples used for the experimental group were SDN Pesaren 02 and the control group was SDN Pesaren 01. Data were collected using test techniques. The results of the study is indicated by the significance value from the t-test, which is 0.000<0.05, meaning there is a difference in the mathematical concept comprehension ability between the experimental group and the control group. The concept comprehension ability of the experimental class reaches average score 85 with the classical completeness reaches 100%. The concept comprehension ability also improves by n-gain of 0.566 with moderate categorized. It can be concluded that Realistic Mathematics Education approach assisted by GeoGebra is effective for student’s concept comprehension ability.